Heterogeneous/Homogeneous Mediators for High‐Energy‐Density Lithium–Sulfur Batteries: Progress and Prospects - Zhang, Ze‐Wen; Peng, Hong‐Jie; Zhao, Meng; Huang, Jia‐Qi (Advanced functional materials, 2018)
Lithium–sulfur (Li–S) batteries deliver a high theoretical energy density of 2600 Wh kg−1, and hold great promise to serve as a next‐generation high‐energy‐density battery system. Great progress has been achieved in cathode design to deal with the intrinsic problems of sulfur cathodes, including low conductivity, the dissolution of polysulfide intermediate, and volume fluctuation. However, aiming at the practical applications of Li–S batteries, the weight percentage of sulfur in cathode materials and the overall areal sulfur loading need to be significantly increased, which inevitably complicate the process and cause heavy shuttle effect, slow redox kinetics, and more undesirable reaction pathways. Recently, rationally designing efficient mediators, as well as incorporating them into a working battery, emerges to be a promising method to construct high‐energy‐density Li–S batteries. The influence of mediators on Li–S batteries appears to be the enhancement in redox kinetics and the increase in reaction efficiency. In this feature article, the mechanistic understanding of redox kinetics in Li–S reactions is discussed, and then a comprehensive analysis of the recent advances in both heterogeneous and homogeneous mediator design is provided. A mediator perspective in building high‐energy‐density Li–S batteries is also included. Mediators in lithium–sulfur batteries can enhance the redox kinetics and increase the reaction efficiency, which benefit the practical applications requiring a high sulfur content and a high areal loading amount. This feature article discusses the mechanism of redox kinetics, and reviews the recent advances in heterogeneous/homogeneous mediator design in lithium–sulfur batteries.